The Persistence of Pagang Gadai in Pusako Tinggi: Embeddedness and Structural Duality in Minangkabau Society - Yetty Oktayanty (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2025)
The practice of pagang gadai at pusako tinggi constitutes a local economic institution that continues to persist within Minangkabau society to the present day. This article aims to analyze the existence of pagang gadai through the perspective of embeddedness ad proposed by Karl Polanyi, which emphasizes that economic activities are inherently embedded in social relations, cultural values and traditional norms. This study based on qualitative research, employing literature review, in depth interviews, participant observation and documentation conducted in West Sumatra. The findings reveal that pagang gadai at pusako tinggi does not merely function as an economic mechanism for cash needs, rather, it reflect values of solidarity, trust and Minangkabau kinship relations. Despite pressure from the modern economic system and formal regulations, this practice persists due to its capacity to adapt to social changes and the strong legitimacy provides by customary institutions.  This article demonstrates that local economic practices such as pagang gadai at pusako tinggi  cannot be separated from the broader social structures in which they are embedded. Therefore, the sustainability of this practice is not solely determined by economic rationality, but also by strength of the social and cultural institutions that support it. Nevertheless, this practice continuously undergoes processes of social reproduction, in which its forms are renegotiated in accordance with changing context over time. Although its manifestations may envolve, the practice has not lost its essential social meaning